ANALISIS KADAR FENOLIK, FLAVONOID DAN AKTIVITAS ANTIOKSIDAN UMBI BAWANG BOMBAI (Allium cepa L.) - Mirwa Adiprahara Anggarani; Rizki Amalia (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2022)
Onions are included in the Alliaceae that is often used as a spice in cooking. Onions have potential as a natural antioxidants. The active compounds that act as antioxidants in onions are phenolic and flavonoid contents. The study aimed to determine the water content, ash content, secondary metabolite compounds, total phenolic contents, total flavonoid contents, and antioxidant activity of the onion bulbs (Allium cepa L.). The extraction method chosen was the multilevel maceration method using three different solvents according to their polarity. The solvents are dichloromethane, ethyl acetate, and 96% ethanol. The total extract obtained from dichloromethane, ethyl acetate, and 96% ethanol solvent was 3,661; 1,476; 72,612. The results showed that onions bulb had a moisture content of 64.7% in the wet form and 5.2% in the powder form. The ash content obtained was 5.64%. Phytochemical screening of onion bulb extracts revealed the presence of flavonoids, saponins, tannins, phenolics, quinones, steroids and triterpenoids. The total phenolic and total flavonoid contents of the onion bulb ethanol extract were 18,245 mg GAE/g extract and 3,381 mg QE/g extract. The IC50 value of the onion bulb ethanol extract is 78.723 μg/mL, which includes in the strong antioxidant group. Key words: onion bulb, total phenolic contents, total flavonoid contents, antioxidant activities